Medicinal products under additional monitoring: a comparative analysis of market access - Radiana Staynova; Desislava Andonova (Folia Medica)
Introduction: In 2010, the European Union (EU) introduced new pharmacovigilance legislation that established an additional monitoring (AM) measure for certain medicines following their marketing authorization. Since 2013, a black inverted triangle (▼), accompanied by a brief explanatory sentence, has been displayed on their leaflet and in the summary of product characteristics. This symbol is uniformly used across all EU member states to indicate medicines subject to AM. Aim: To analyze the medicines under AM listed by the European Medicines Agency (EMA) and compare them with those available on the pharmaceutical market in Bulgaria. Material and methods: A descriptive analysis was performed on the EMA’s list of medicines under AM as of February 23, 2024 (EMA/245297/2013 Rev. 119). Additionally, the study assessed the market access and affordability of these medicines in Bulgaria by examining their inclusion in the Positive Drug List (PDL). Public electronic registers of the National Council on Prices and Reimbursement of Medicinal Products in Bulgaria were used for this analysis. Results: The EMA’s list comprised a total of 358 medicines, of which 90 were available on the Bulgarian pharmaceutical market as of February 2024. The analysis revealed that the majority of these medicines were new active substances (n=27, 30%), new biologicals (n=12, 13.3%), and medicines requiring post-authorization safety studies, PASS (n=21, 23.3%). Conclusion: Notably, only 25% of medicines under AM authorized in the EU were marketed in Bulgaria, with a significant proportion of these being new active substances, particularly in therapeutic areas such as oncology, hematology, and neurology.